Emergent Scale-free Social Networks in History: Burning and the Rise of English Protestantism - Ormerod Paul; Roach Andrew P. (Cultural Science)
There is a large and rapidly increasing literature which analyses social networks for which substantial amounts of quantitative data are available. Further, there is a growing and related literature on what is referred to by economists as ‘information cascades’ on such networks.